Ku liberalizmowi otwartemu - LEKKA-KOWALIK, Agnieszka (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
Recenzja: W. Ver Eecke, Ethical Dimension of the Economy: Making Use of Hegel and the Concepts of Public and Merit Goods, Springer Verlag, Berlin–Heidelberg 2008.